"La Secchia rapita" di Alessandro Tassoni i fondamenti della comicità del testo tassoniano - Májková, Markéta (2006)
Alessandro Tassonis THE RAPE OF THE BUCKET. The comicity basis of the text. Analysis of the most known italian baroque epic text of the comic character. A short view into the italian baroque literature, character of the genre.